2023
DOI: 10.1007/s11030-023-10636-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FDA-approved drugs with triple targeting mode of action for the treatment of monkeypox: a high throughput virtual screening study

Abstract: According to the Center for Disease Control and Prevention, as of August 23, 94 countries had confirmed 42,954 Monkeypox Virus cases. As specific monkeypox drugs are not yet developed, the treatment depends on repurposed FDA-approved drugs. According to a recent study, the Monkeypox outbreak is caused by a strain with a unique mutation, raising the likelihood that the virus will develop resistance to current drugs by acquiring mutations in the targets of currently used drugs. The probability of multiple mutati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Based on the high docking score only four compounds, namely, (3R,5S)-3-[(3S,5S,9R,10S,13S,14R,16R,17R)-16-hydroxy-10,13-dimethyl-3-[(2R,3S,4S,5R,6S)-3,4,5-trihyd, [(2S, 3S,6E,10E,14E,18R)-2,3,18,19-tetrahydroxy-2,6,11,15,19-pentamethyl-icosa-6,10,14-trienyl], 8-oxo-16-[(2R,3S,4S,5S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)tetrahydropyran-2-yl]oxy-hexadecanoic, (2R)-2-[(3S, 4S)-3,4-dihydroxy-2,2-dimethyl-8-(4-methylpent-3 -enoxy)chroman-6- yl]-5,7-dihydroxy-chrom with a docking score of −6.55 kcal/mol, −6.47 kcal/mol, −6.37 kcal/mol and −6.35 kcal/mol respectively. A similar approach has been used by the previous study which uses the FDA approved drugs against the three different targets such as topoisomerase1, p37, and thymidylate kinase of the monkey pox virus ( Srivastava et al, 2023 ). Another study used drug screening against monkey pox virus cysteine proteinase ( Odhar, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the high docking score only four compounds, namely, (3R,5S)-3-[(3S,5S,9R,10S,13S,14R,16R,17R)-16-hydroxy-10,13-dimethyl-3-[(2R,3S,4S,5R,6S)-3,4,5-trihyd, [(2S, 3S,6E,10E,14E,18R)-2,3,18,19-tetrahydroxy-2,6,11,15,19-pentamethyl-icosa-6,10,14-trienyl], 8-oxo-16-[(2R,3S,4S,5S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)tetrahydropyran-2-yl]oxy-hexadecanoic, (2R)-2-[(3S, 4S)-3,4-dihydroxy-2,2-dimethyl-8-(4-methylpent-3 -enoxy)chroman-6- yl]-5,7-dihydroxy-chrom with a docking score of −6.55 kcal/mol, −6.47 kcal/mol, −6.37 kcal/mol and −6.35 kcal/mol respectively. A similar approach has been used by the previous study which uses the FDA approved drugs against the three different targets such as topoisomerase1, p37, and thymidylate kinase of the monkey pox virus ( Srivastava et al, 2023 ). Another study used drug screening against monkey pox virus cysteine proteinase ( Odhar, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been used by the previous study which uses the FDA approved drugs against the three different targets such as topoisomerase1, p37, and thymidylate kinase of the monkey pox virus (Srivastava et al, 2023). Another study used drug screening against monkey pox virus cysteine proteinase (Odhar, 2022).…”
Section: Figurementioning
confidence: 99%
“…The nucleotide stretch identified in the monkeypox genome has 99.19% similarity with the p37 gene of the vaccinia virus. [ 25 ] The protein sequence (372 amino acids) of MPV p37 was obtained through the translation of gene sequence using the Expasy server (https://web.expasy.org/translate/). In the protein–protein blast study, the protein sequence has shown 99.9% identity with p37 of the Vaccinia virus.…”
Section: Methodsmentioning
confidence: 99%
“…[ 26 ] The interacting amino acid residues of Monkeypox's p37 protein were identified by sequence alignment with p37 of the vaccinia virus. [ 25 ] The p37 modeled structure was validated by evaluating the conformational orientation, QMEAN score, and global model quality estimation (GMQE) through the structure assessment tool and Ramachandran plot. GMQE scores range from 0 to 1, with higher scores indicating more reliable models.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al (2022a) found that the F13 sequence is highly conserved in MPXV and VARV, and similarity ranges from 97.58% to 99.73%. Similarly, Srivastava et al (2023) conducted a protein-protein blast analysis, revealing a sequence alignment similarity of 99.9% between MPXV and VACV. As a result, tecovirimat, formerly approved for treating smallpox, has shown potential for treating mpox.…”
Section: Eev Proteins F13mentioning
confidence: 99%